VERNAKULARISASI AL-QUR'AN: UPAYA PELESTARIAN BAHASA TOLAKI MELALUI PENERJEMAHAN (Al-Qur’an Vernacularization: Attempt of Tolaki Language Preservation Through Translation) - Gunawan, Fahmi (Kandai, 2024)
The present study aims to analyze the process of translating the Qur'an into Tolaki. Data were collected through in-depth interviews, participant observation, and document analysis. Analysis was conducted using Hans J. Vermeer's Skopos theory. The findings indicate that the translation process of the Qur'an into Tolaki is tailored to the translation's purpose, utilizing Indonesian as the source language. The predominant translation ideology favors foreignization over domestication; the method employed is more inclined towards semantic rather than communicative translation. The prevalent levels of speech include 'anakia' and 'iwawo', and Arabic is sometimes used to clarify ambiguous meanings in Indonesian. Consequently, this study underscores the importance of adapting sacred texts to local social and cultural contexts. This adaptation involves selecting methodologies sensitive to the nuances of Tolaki society and employing language strategies that preserve authenticity and religious relevance. As a result, this translation serves as an effective communication tool and a symbol of the integration of religious and cultural identities in the lives of the Tolaki people. Penelitian ini bertujuan untuk menganalisis proses penerjemahan Al-Qur'an ke bahasa Tolaki. Wawancara mendalam, observasi partisipan dan analisis dokumen digunakan dalam mengumpulkan data. Analisis data dilakukan dengan menggunakan teori Skopos Hans J Vermeer. Hasil penelitian melaporkan bahwa proses penerjemahan Al-Qur'an ke bahasa Tolaki disesuaikan dengan tujuan penerjemahan, penggunaan bahasa Indonesia sebagai bahasa sumber, ideologi penerjemahan lebih dominan menggunakan ideologi forenisasi daripada domestikasi, metode penerjemahan lebih cenderung menggunakan penerjemahan semantik daripada penerjemahan komunikatif, level tuturan lebih dominan menggunakan tuturan anakia dan iwawo, serta bahasa Arab terkadang digunakan sebagai konfirmasi lanjutan mengenai makna kurang jelas di dalam bahasa Indonesia. Dengan demikian, penelitian ini mengimplikasikan pentingnya adaptasi teks suci sesuai dengan konteks sosial dan kultural lokal. Proses ini melibatkan pemilihan metodologi yang sensitif terhadap nuansa masyarakat Tolaki dan penggunaan bahasa untuk menjaga autentisitas dan relevansi religius. Hasilnya, terjemahan ini menjadi alat komunikasi yang efektif dan simbol integrasi identitas keagamaan dan budaya dalam kehidupan masyarakat Tolaki.